Makna Filsafat dan Saintifik dalam Keimanan - Rohmatallah, Syahrul; Farih, Awan; Anbari, Hilman; Rosa, Andi (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
The study of faith in philosophical and scientific contexts is an attempt to understand the spiritual dimension of human beings from different perspectives. In philosophy, faith is explored through in-depth questions about the existence of God, the relationship between faith and reason, and the moral values ​​that arise from faith. This approach encourages individuals to think about the nature of their beliefs and enforce them in everyday life. Meanwhile, the scientific approach emphasizes the empirical aspects of faith, focusing on its impact on mental health, social behavior, and religious experience. Research in psychology, sociology, and neuroscience offers insights into how faith affects the lives of individuals and groups, and how religious experiences can be explained through a scientific lens. The combination of philosophical and scientific approaches to understanding faith not only enriches discussions about faith but also provides a foundation for constructive dialogue between religion and science. By understanding faith from both perspectives, we can explore deeper and more relevant meanings, and bridge the gap between spiritual beliefs and scientific knowledge. This article aims to examine the interaction between philosophy and science related to faith, and its strengthening for individuals and society in facing the challenges of modern life. Keywords faith in the Quran and philosophy, science.